Diabetes insipidus secondary to tuberculous meningoencephalitis with hypothalamic involvement extending to the hypophysis: a case report - Monique Freire Santana; Guilherme Augusto Pivoto João; Marcus Vinicius Guimarães de Lacerda; Luiz Carlos de Lima Ferreira (Revista da Sociedade Brasileira de Medicina Tropical)
Abstract The involvement of Mycobacterium tuberculosis in the central nervous system (CNS) is an uncommon and devastating manifestation of tuberculosis. We report a case of disseminated tuberculosis presenting as meningoencephalitis, hypothalamic involvement with extension to the hypophysis, and secondary insipidus diabetes diagnosed at autopsy.